Outcomes of Gel Stent Implantation for Glaucoma in Patients With Previous Corneal Graft Surgery: A Case Series. Issue 4 (April 2020) - Rahmania, Nesrine; Rampat, Radhika; Moran, Sarah; Gatinel, Damien; Grise-Dulac, Alice
Abstract : Purpose: To report a series of 5 cases with successful placement of a minimally invasive glaucoma surgery (MIGS) device for glaucoma refractory to medical management in patients with previous corneal grafts. Methods: This is a retrospective analysis of all cases with a Xen45 Gel Stent (Allergan plc, Dublin, Ireland) for ocular hypertension and glaucoma refractory to medical treatment after corneal graft surgery between 2016 and 2019 at the Rothschild Foundation, Paris. We did the imaging studies and studied the intraocular pressure (IOP) and the endothelial cell count preimplantation and postimplantation with a MIGS device. Results: Five cases were included in this study, demonstrating a well-tolerated, highly effective, and sustained method for controlling the IOP, which was refractory to previous treatment. An average IOP reduction of 70.5% was noted with a needling rate of 20%, and no adverse events were noted except 1 IOP spike day 7 post-op with no long-term effects. Conclusions: Glaucoma after graft surgery is a well-known and devastating complication, and as numbers of graft surgery performed increases, so will the incidence of glaucoma. MIGS devices such as the Xen45 Gel Stent (Allergan plc) should become a part of our accepted armory to treat raised IOP refractory to medical treatment without delay. Abstract : Supplemental Digital Content is Available in the Text.